Rural public acceptance of wind and solar energy: a case study from Mersing, Malaysia - Mohd Safari, Muhammad Aslam; Masseran, Nurulkamal; Jedi, Alias; Mat, Sohif; Sopian, Kamaruzzaman; Abdul Rahim, Azman; Zaharim, Azami (Multidisciplinary Digital Publishing Institute (MDPI), 2020)
The sustainable development of the energy sector through the implementation of renewable energy (RE) technology has been a primary concern for the government of Malaysia since the 1990s. Developing RE technology in rural areas is also one of the most important energy strategies. One of the most important requirements for the successful adoption of renewable energy technology is the public acceptance of this technology. This article examines the public acceptance of RE (wind and solar) technologies among rural residents in Mersing, Malaysia. This study is conducted in conjunction with the development of the hybrid wind–solar RE generation system for the Marine Ecosystem Research Centre (EKOMAR), which located in Mersing. To investigate the public acceptance of RE technologies, two surveys were conducted, before and after the installation of the hybrid wind–solar RE generation system. The findings revealed that RE innovations, such as wind and solar energy, were well known among 54.7% and 96.2% of the respondents, respectively, before and after the introduction of EKOMAR. The survey results showed that rural residents generally support RE technologies and EKOMAR RE projects. They were also in line that the use of RE should also be extended to other parts of Mersing, including wind and solar. These findings illustrate that EKOMAR has played a crucial role in educating local residents about RE, wind and solar energy in particular. Residents believe the government plays an important role, particularly in rural areas, in encouraging and enhancing RE technologies.